An Autism-Associated Neuroligin-3 Mutation Affects Developmental Synapse Elimination in the Cerebellum - Lai, Esther Suk King; Nakayama, Hisako; Miyazaki, Taisuke; Nakazawa, Takanobu; Tabuchi, Katsuhiko; Hashimoto, Kouichi; Watanabe, Masahiko; Kano, Masanobu (Frontiers in Neural Circuits, 2021)
Neuroligin is a postsynaptic cell-adhesion molecule that is involved in synapse formation and maturation by interacting with presynaptic neurexin. Mutations in neuroligin genes, including the arginine to cystein substitution at the 451st amino acid residue (R451C) of neuroligin-3 (NLGN3), have been identified in patients with autism spectrum disorder (ASD). Functional magnetic resonance imaging and examination of post-mortem brain in ASD patients implicate alteration of cerebellar morphology and Purkinje cell (PC) loss. In the present study, we examined possible association between the R451C mutation in NLGN3 and synaptic development and function in the mouse cerebellum. In NLGN3-R451C mutant mice, the expression of NLGN3 protein in the cerebellum was reduced to about 10% of the level of wild-type mice. Elimination of redundant climbing fiber (CF) to PC synapses was impaired from postnatal day 10 to 15 (P10 to 15) in NLGN3-R451C mutant mice, but majority of PCs became mono-innervated as in wild-type mice after P16. In NLGN3-R451C mutant mice, selective strengthening of a single CF relative to the other CFs in each PC was impaired from P16, which persisted into juvenile stage. Furthermore, the inhibition to excitation (I/E) balance of synaptic inputs to PCs was elevated, and calcium transients in the soma induced by strong and weak CF inputs were reduced in NLGN3-R451C mice. These results suggest that a single point mutation in NLGN3 significantly influences the synapse development and refinement in cerebellar circuitry, which might be related to the pathogenesis of ASD.